Clinico-radiologic evaluation of new onset seizures in children presenting to the tertiary care hospital; a descriptive cross-sectional study - Rukhsana Aziz; Parvaiz, Hina; Nosheen Noor; Zenab Rehman; Wasq Raza; Muhammad Shoaib (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the clinical and radiological spectrum of new onset seizures in children, and to determine outcomes in such cases. Method: The cross-sectional study was conducted at the Paediatric Department of Medical Teaching Institute Lady Reading Hospital Peshawar, Pakistan, from November 1, 2023. to April 30, 2024, and comprised children aged from one month to 15 years presenting with new onset seizures regardless of aetiology. Data was collected using a semi-structured questionnaire. Data was analysed using SPSS 27. Results: Of the 156 patients with mean age 1.91±1.025 years, 99(63.5%) were boys and 57(36.5%) were girls. Fever was present in 129(82.7%) children at presentation, while 27(17.3%) presented with status epilepticus. Multivariable logistic regression showed that focal neurological deficit was a significant predictor of poor outcome (p<0.02; odds ratio: 2.98, 95% confidence interval: 1.178-7.57). Conclusion: Among several predictors of poor outcome in children with new onset seizures, focal neurological deficit was the most significant. Key Words: Seizures, Paediatric, Neuroimaging, Meningitis, Hydrocephalus, Infarct.